Pengaruh Kesadaran Wajib Pajak, Sanksi Pajak, dan Tarif Pajak Terhadap Kepatuhan Wajib Pajak UMKM di Kecamatan Denpasar Timur - Setyawati, Ni Putu Juli; Kusumawati, Ni Putu Ayu; Pramuki, Ni Made Wisni Arie (Hita Akuntansi dan Keuangan, 2025)
This research aims to analyze factors that can influence taxpayer compliance. The independent variables in this research are taxpayer awareness, tax sanctions, and tax rates, while the dependent variable in this research is MSME taxpayer compliance. Respondents in this research were MSME taxpayers in East Denpasar District. This research uses a quantitative method where data is obtained from distributing questionnaires to 369 respondents using a probability sampling method using a simple random sampling technique. The data analysis technique used in this research is PLS-SEM analysis. The type of data used in this research is primary data. The primary data source in this research was collected directly from taxpayers in Micro, Small and Medium Enterprises (MSMEs) in East Denpasar District. The results of the research show that taxpayer awareness and tax sanctions have a positive and significant effect on MSME taxpayer compliance in East Denpasar District. Meanwhile, tax rates have a negative and insignificant effect on MSME taxpayer compliance in East Denpasar District.